2009
DOI: 10.1002/ajmg.b.30988
|View full text |Cite
|
Sign up to set email alerts
|

Parkin gene modifies the effect of RLS4 on the age at onset of restless legs syndrome (RLS)

Abstract: A co-occurrence of restless legs syndrome (RLS) and Parkin mutations has been described. In South Tyrolean RLS patients, a novel RLS locus has been found (RLS4) and recurrent Parkin mutations have been reported. By a systematic screen we investigated the presence of founder Parkin mutations in South Tyrolean RLS patients with known carrier status at the RLS4 locus and assessed whether these mutations alone or in combination influence the RLS phenotype measured by three quantitative RLS traits (age at onset (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…On the other hand, RLS as well as PD responds to dopaminergic agents and a positive response to levodopa supports the diagnosis of both conditions. In addition, a cooccurrence of RLS and Parkin mutations (that are associated with familial parkinsonism) has been described50 and the authors were able to show that the presence of a heterozygous Parkin mutation in RLS patients linked to RLS4 can lower the age at onset of RLS 51. Taken together, these data suggest a possible connection between both diseases, although more accurate assessments are necessary.…”
Section: Overview Of the Pathology Of Restless Legs Syndromementioning
confidence: 82%
“…On the other hand, RLS as well as PD responds to dopaminergic agents and a positive response to levodopa supports the diagnosis of both conditions. In addition, a cooccurrence of RLS and Parkin mutations (that are associated with familial parkinsonism) has been described50 and the authors were able to show that the presence of a heterozygous Parkin mutation in RLS patients linked to RLS4 can lower the age at onset of RLS 51. Taken together, these data suggest a possible connection between both diseases, although more accurate assessments are necessary.…”
Section: Overview Of the Pathology Of Restless Legs Syndromementioning
confidence: 82%
“…Although conventional linkage as well as genomewide association studies have identified more than ten genomic loci associated with each disease [21,58,59,61,62,70,71], none of these loci overlap. Still, it has been shown that a heterozygous deletion of exon 7 of the PD-associated PARKIN gene advanced the age of disease onset in cases of familial RLS linking to the RLS4 locus by 16.9 years (p = 0.0016) [50]. On the contrary, no association of the RLS-linked single-nucleotide polymorphisms (SNPs) [59,62,70] with the PD phenotype could be found in 396 PD patients and 403 unrelated controls belonging to a cohort in the USA [67].…”
Section: Rlsmentioning
confidence: 99%